PENGARUH PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) TERHADAP HASIL BELAJAR KARAKTERISTIK MIKROORGANISME - Asti Juniastuti; Kadirman Kadirman; Muhammad Rais (Universitas Negeri Makassar, 2016)
This research is a quasi experimental research that aims to determine the effect of the use of cooperative learning type NHT ( Numbered Heads Together ) to improving student learning outcomes TPHP class X SMK 3 Takalar. The population in this research was all students of class X SMK 3 Takalar. The sample consists of two classes. There are 25 students in every class, class X2 as the experimental group and the class X1 as the control group. This research using random sampling techniques. Methods of collection data using observation, test, documentation and questionnaires. Method in this research using descriptive statistical analysis and inferential analysis. The results of this research showed that the value of post-test experimental group was higher than post-test control group, so that implementation of cooperative learning model NHT significant effect on learning outcomes characteristics of the microorganism class X SMK 3 Takalar